Inflation - Einzig, Paul. (London : Chatto and Windus, 1952)
This book examines early history of inflation and attempt to deal with its subject from both theory and practice. The book was primarily concerned with the British post-war experience, it also contains frequent reference to post-war experience in the United States and other countries.
Includes index
usc 21/06/18
Loans
Keywords: Inflation (Finance)